Mrs. Fred May and Mrs. LeRoy Schwaerer - Unknown:::Creator::::::::::::
Photograph is of Mrs. Fred May and Mrs. LeRoy Schwaerer who are standing and looking at something in a folder they are both holding. They are nicely dressed and Mrs. May has a corsage on her sweater.